Species and cultivars of lilac (Syringa L.) recommended for ornamental gardening in the Republic of Bashkortostan - N. V. Polyakova (Аграрная наука Евро-Северо-Востока, 2025)
Lilac, as one of the most decorative and unpretentious to growing conditions shrubs, is very popular in landscape industry. Comprehensive introduction studies on the formation of an assortment of Syringa L species and cultivars resistant to the conditions of the Bashkir Cis Urals were conducted from 1999 to 2024. The research area belongs to the 3rd zone of plant endurance, the climate is continental. The objects of the research were 260 lilac taxa from the collection of the South Ural Botanical Garden-Institute of the UFIC RAS. According to generally accepted methods of phenological observations and winter hardiness, there have been identified 10 species, 52 cultivars of common lilac and 3 cultivars of hyacinthocolor lilac, which have successfully passed acclimatization and consistently show decorative signs at maximum values. Data on the size of the bush of each taxon, the timing and duration of flowering, color, shape and size of flowers and inflorescences are provided. Recommendations are given on variants for the use of lilac species and cultivars in landscape design. These lilac taxa can be recommended for further use in landscaping settlements of the Bashkir Cis Urals and adjacent regions.